Microstructure of thermoelectric (Bi0.15Sb0.85)2Te3 film - Yildiz, Koksal; Akgul, Unal; Leipner, Hartmut S.; Atici, Yusuf (Springer, 2014)
The film of thermoelectric ternary p-type (Bi0.15Sb0.85)(2)Te-3 was deposited on polyimide foil substrate at 168 degrees C using direct-current magnetron sputtering. Microstructural investigations of the film were performed by electron microscopy techniques. SEM observations showed that the film surface consisted of large-sized particulates with small-sized particles and also mound-like crystal agglomerates in some areas. Chemical composition of the film was analyzed using energy-dispersive X-ray spectrometer (EDS). It has been observed that the EDS results were in an agreement with nominal composition for the film. Detailed microstructural investigations were carried out using transmission electron microscopy (TEM). TEM images and selected area electron diffraction patterns showed that the film has randomly oriented polycrystalline grain structure. High-resolution TEM images indicated that the microstructure of film also contained nano-crystal structure, smaller than 10 nm.
Keywords: Thin-Films; Electrochemical Deposition; Merit; Figure; Performance; Electrodeposition; Nanostructures; Devices; Alloys